201 Age-Associated Decline in Nav1.4 and Nav1.5 Isoforms of the Sodium Channel in Rat Heart. (6th June 2015) - Cooper, Stephanie; Jones, Sandra
Abstract : Voltage-gated sodium channels (VGSCs) generate the Na + current (INa ) responsible for the cardiac action potential upstroke largely due to the 'cardiac' isoform Nav 1.5, but other isoforms are responsible for ˜20% of the upstroke and a component of a sustained sodium current. This sustained component has been attributed with an increasing arrhythmia risk, particularly within the elderly and has been the target of development for new anti-arrhythmic drugs. Our study has investigated the age-associated changes in protein density and localisation of the VGSC alpha-subunits Nav 1.5 and Nav 1.4 in the rat heart. Rats at 6, 12 and 28 months of age were sacrificed, their hearts dissected into the regions of left and right ventricle, left and right atria, epicardium and endocardium (n = 5). These regions were analysed by western blot to determine the protein expression of Nav 1.5 and Nav 1.4 (Alomone, Israel), normalised to the expression of desmin (Dako, UK). Immunocytochemistry of single cardiac myocytes was used to observe the protein distribution and location of Nav 1.5 and Nav 1.4 conjugated to Alexa 488 (Molecular probes, UK), and cellular membranes were labelled by wheat germ agglutinin conjugated to rhodamine (Vector, UK), viewed by confocal microscopy (Zeiss 710, Germany). Ethical approval was given by the University of Hull. Mean±SEM. Nav 1.5 protein was expressed at the lateral membrane, intercalated disk and t-tubular membrane in single myocytes. When examining the tissues, the relative expression of Nav 1.5 was significantly reduced with age (ANOVA, p = 0.01). It was determined Nav 1.5 protein expression in the right atria was at 6 months (100 ± 12.3%) and similar at 12 months, however at 24 months there was a significant decline to 50 ± 8.65% (Student T-test, Bonferroni adjustment <p = 0.006). Intense punctate labelling of intercalated disks was observed with Nav 1.4, and a similar significant decline in right atrial protein expression observed at 24 months (ANOVA, p = 0.05). We conclude that there is an age-dependent decline in both Nav 1.5 and Nav 1.4 within the right atria, possibly contributing towards arrhythmia generation in the elderly, however the underlying mechanisms remain unclear.